Up to Maughty London : Joyce's Cultural Capital in the Imperial Metropolis - Loukopoulou, Eleni (Book collections on Project MUSE., 2017)
This book examines the largely under-explored connection between Joyce's writings, their publication history, and the city of London, arguing that the metropolis was an important political and cultural center for Joyce.